Spotlight 5: Great Meteor Seamount - Christian Mohn (Oceanography, 2010)
Great Meteor Seamount is one of the largest seamounts in the Atlantic Ocean, rising from 4200-m depth at the seafloor to 270-m depth beneath the sea surface. Its elliptical plateau encompasses an area of 1500 km2, roughly matching the size of the Spanish island of Gran Canaria. There is a long tradition of multidisciplinary research at Great Meteor Seamount, dating back to 1967. It has become one of the best-studied seamounts globally, with research aimed at better understanding the connections between oceanic motion around seamount structures and biological distribution patterns. Meincke (1971) was the first to identify a circulation system in the form of an anticyclonic vortex trapped atop Great Meteor Seamount, with the potential to accumulate mesopelagic zooplankton, micronekton, and even fish species with weak swimming capabilities. Later studies revealed a more complex flow spectrum at the seamount, dominated by tidal and internal tidal motions and a high level of spatial and temporal variability. These findings, together with similar studies at other seamounts, indicate that seamounts play a role in ocean biology far beyond the classical view of particle retention inside stationary and closed circulation cells.